Intensifikasi Pekarangan dengan Tanaman Obat sebagai Ecotherapy dan Peningkat Imunitas - Joko Sutrisno; Agustono Agustono; Rhina Uchyani Fajarningsih; Refa'ul Khairiyakh; Amalia Nadifta Ulfa; Indah Nurhidayati (AgriHealth, 2021)
Corona Virus Disease 19 (COVID-19) is a disease caused by the SARS-CoV-2 virus that can be transmitted between humans through coughing or sneezing. The application of health protocols and increased immunity is an effort to prevent COVID-19 infection. Intensification of home garden with immune-boosting medical plants have several benefits, that are the fulfillment of household needs of immune-boosting medical plants, overcome the soaring price of immune-boosting medical plants and as physical activity and community ecotherapy to increase immunity. Community service with theme intensification of home garden with immune-boosting medical plants and as ecotherapy was carried out in Mojolaban Sub-district, Sukoharjo. The community service aimed to improve the knowledge and skills of the community related to the intensification of home garden medical plants that can be used as ecotherapy. This activity was conducted by extension and training methods to representatives of two Farmer Women’s Groups, namely KWT Sri Rejeki and KWT Mekar Sari. Participants of this community activity look enthusiastic to follow each activity. The team of community service activity in Mojolaban Sub-district also handed over tools and materials in form of planting media, fertilizers, medical plants seed (turmeric, ginger, temulawak and lemongrass) to KWT Sri Rejeki and KWT Mekar Sari for starting the intensification of home garden with immune-boosting medical plants. This community service increases the knowledge of the community in Mojolaban Sub-district about the intensification of home gardens with immune-boosting medical plants, the community is also enthusiastic to conduct home garden intensification with immune-boosting medical plants after knowing of benefits that will be obtained.